Coordination of dendritic inhibition through local disinhibitory circuits - Francavilla, Ruggiero; Luo, Xiao; Magnin, Elise; Tyan, Leonid; Topolnik, Lisa (Frontiers in Synaptic Neuroscience, 2015)
It has been recognized for some time that different subtypes of cortical inhibitory interneurons innervate specific dendritic domains of principal cells and release GABA at particular times during behaviorally relevant network oscillations. However, the lack of basic information on how the activity of interneurons can be controlled by GABA released in particular behavioral states has hindered our understanding of the rules that govern the spatio-temporal organization and function of dendritic inhibition. Similar to principal cells, any given interneuron may receive several functionally distinct inhibitory inputs that target its specific subcellular domains. We recently found that local circuitry of the so-called interneuron-specific (IS) interneurons is responsible for dendritic inhibition of different subtypes of hippocampal interneurons with a great impact on cell output. Here, we will review the properties and the specificity of connections of IS interneurons in the CA1 hippocampus and neocortex, and discuss their possible role in the activity-dependent regulation of dendritic inhibition received by pyramidal neurons.